Effects of 17β-estradiol and tamoxifen on the induction of chromosomal abnormalities and on the expression of her2 gene in breast cancer cell lines (2014)
This study covers an area of great importance in the research of breast cancer, related to the study of the effects of both estrogens (E2) and anti-estrogens (Tamoxifen) on chromosomes and of modulation of gene expression. Considering that breast cancer is a very heterogeneous disease and that patients respond differently to treatment, the identification of chromosomal abnormalities as well as genes responsive to 17β-estradiol (E2) and Tamoxifen (TAM) could provide the necessary framework to understand the complex effects of this hormone in target cells and could explain, at least in part, the development of cellular resistance to TAM treatment and the subsequent best therapeutic option. In this order of ideas, we determined the effects of E2 and TAM on the chromosomes and on the modulation of gene expression in four breast cancer cell lines, which represent three of the five subtypes of breast cancer known at present. The results are presented in six chapters - each one has a group of the results achieved around the cytogenetic characteristics and gene expression profiles of four cell lines and the effects of E2 and TAM incubation on those. The first chapter describes the main features of breast cancer, furthering the use and effects of E2 and TAM treatment.